PENGARUH INTERNAL CONFLICT TERHADAP KINERJA PEGAWAI DAN ORGANIZANIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MEDIASI - Marisi P. Manalu; Ana Sriekaningsih; Diki Diki (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The research objectives to be achieved from this research are to analyze and prove: The effect of internal conflict on Organizational Citizenship Behavior, the influence of Organizational Citizenship Behavior on employee performance, the influence of internal conflict on employee performance and the influence of Organizational Citizenship Behavior variable as a mediating variable between internal conflict on performance. employees at the Tarakan Class III Port Authority and Harbormaster Office. This study uses a quantitative descriptive research approach, where this study will describe a number of variables related to the problem and unit under study among the phenomena being tested. The population in this study were all employees at the Port Authority and Class III Tarakan Port Authority totaling 64 employees. The sample of this study was 47 who were employees of the Class III Port Authority and Port Authority of Tarakan. For data analysis in this study using the help of the SmartPLS software. The results showed that the internal conflict variable did not have a significant effect on OCB, meaning that the first hypothesis in this study was rejected. The OCB variable has a positive and significant effect on employee performance, meaning that the second hypothesis in this study is accepted. The internal conflict variable has a positive and significant effect on employee performance, meaning that the third hypothesis in this study is accepted. The OCB variable is not an intervening variable between internal conflict and employee performance at the Port Authority and Port Authority Class III Tarakan